Differences in the released endothelial microparticle subtypes between human pulmonary microvascular endothelial cells and aortic endothelial cells in vitro. (1st May 2013) - Takahashi, Toru; Kobayashi, Seiichi; Fujino, Naoya; Suzuki, Takaya; Ota, Chiharu; Tando, Yukiko; He, Mei; Yamada, Mitsuhiro; Kurosawa, Shin; Yamaya, Mutsuo; Kubo, Hiroshi
ABSTRACT Circulating endothelial microparticles (EMPs) are membrane vesicles that are shed into the blood stream from activated or apoptotic endothelial cells. We previously reported that circulating EMP numbers significantly increased in stable chronic obstructive pulmonary disease (COPD) patients and during exacerbation compared with healthy control subjects. However, different types of circulating EMPs with distinct time profiles were detectable during exacerbations. We hypothesized that the released EMP subtypes correlated with differences in the inflammatory stimuli and the endothelial cell type. We compared the EMP subtypes from human aortic endothelial cells (Aortic ECs) and human lung microvascular endothelial cells (Pulmonary microvascular ECs) released in response to various stimuli, including proinflammatory cytokines (TNFα), oxidative stress (H2O2), and cigarette smoke extracts (CSE) in vitro. We defined circulating EMPs by the expression of endothelial antigens: CD144+ MPs (VE-cadherin EMPs), CD31+/CD41− MPs (PECAM EMPs), CD62E+ MPs (E-selectin EMPs), and CD146+ MPs (MCAM EMPs). E-selectin EMPs were released from both pulmonary microvascular and aortic ECs in response to TNFα but not to H2O2 or CSE stimulation. The amount of MCAM EMPs released from pulmonary microvascular ECs differed significantly between the cells stimulated with H2O2 and those stimulated with CSE. VE-cadherin EMPs were only released from aortic ECs, whereas PECAM EMPs were released exclusively from pulmonary microvascular ECs. The EMP subtypes released differ in vitro among TNFα, H2O2, and CSE stimulation as well as between pulmonary microvascular and aortic ECs. The differences in circulating EMP subtypes may reflect a condition or site of endothelial injury and may serve as markers for endothelial damage in COPD patients.